Realtime Filtering of Waste Separate Equipment in Irrigation Channels - Sumardi Sadi; Iqbal Majid Zulvikar (PT FORMOSA CENDEKIA GLOBAL, 2022)
There are still many people who are not aware of disposing of waste in its place, including littering, one of which is in irrigation canals which can clog the channels and the many types of waste that can be found. To reduce waste in irrigation canals, an automatic waste separator was made. This automatic waste separator aims to transport waste in irrigation canals using two stages of conveyors, namely conveyor 1 for conveying lines from under water and conveyor 2 for waste separation lines, after which the waste is separated. according to the category, namely by using an inductive proximity sensor for Metal Waste and will be separated by using a servo motor, for non-metallic waste will be allowed to run on conveyor 2 then the waste is put into a trash can which can be monitored by ultrasonic sensors to see the height of the contents of the bin the trash. Monitoring this garbage separator uses the NodeMCU ESP 8266 WIFI as a connector with the BLYNK application to see whether the contents of the trash can are full or not by the cleaning officer on duty then the full trash can will be replaced with an empty trash can with monitoring control via BLYNK.